Implementasi Algoritme Speck untuk Enkripsi dan Dekripsi pada QR Code - Yuniar Siska Fatmala; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Along with the development of technology, emerging new technologies are predicted to replace the function of the barcode. The technology is QR code technology. Quick Response Codes or QR codes are two-dimensional barcodes developed by Denso Wave Corporation in 1994. The QR Code is capable of storing information that is large enough therefore the QR Code needs to be secured because currently there is a lot of piracy of a code, which will harm someone or a related agency. There are several efforts to maintain data confidentiality so that it is not misused, one of which is by implementing the SPECK algorithm. SPECK is a family of lightweight blockcipers published by the U.S. National Security Agency. in 2013. From the results of the SPECK algorithm implementation can be concluded that this application can encrypt all types of characters in the form of strings, letters, numbers or symbols that need to be secured, and when decrypting the QR Code the application will activate the camera function and scan the QR Code that will become plainntext again. This is evidenced in security testing which proves that the results of ciphertext are very different from plaintext. The execution time of encryption and decryption can be proven by testing the performance of encryption time with the total performance required time is 0.061614036560059 seconds and in testing the performance of the decryption time total performance of the time taken is 0.0039241313934326 seconds.